Mitigation of Power Oscillations in a Quad Active Bridge with Gha-Based Modeling and Hepta-Phase-Shift Modulation - Espina-Gonzalez, E (IEEE Computer Society, 2024)
This article introduces a new method for mitigating low frequency power oscillations in a Quad Active Bridge (QAB) converter. This is achieved by using GHA-based frequency-domain modeling of the QAB to obtain an equivalent model that considers Hepta Phase Shift (Hep-PS) modulation, utilizing all seven degrees of control possible in the QAB. The model is used in the creation of an optimization problem with a conduction loss minimization approach, which generates optimal solutions of the seven degrees of control (duty cycles and phases) for multiple operating points (port voltages and transfer powers). The results are stored in a look-up table (LUT). The control and modulation are validated in a PLECS simulation, achieving equal and different power flows in an asymmetrical QAB connected to variable voltage primary ports and a single fixed voltage secondary port. The presented method optimizes converter efficiency by minimizing conduction losses, allows the use of smaller capacitors, and helps to prevent saturation of the HFT while reducing its size and losses. © 2024 IEEE.